Hypertension and diabetes on cognitive impairment: a case–control study in China - Jing Wu; Xiangjun Yin; Weiqiang Ji; Yang Liu; Jing Tang; Han Zhang; Shige Qi; Jie Li; Li Lin; Xueqing Yang; Chengdong Xu; Qingfeng Du (Alzheimer’s Research & Therapy)
Abstract Background Cognitive impairment, hypertension and diabetes are prevalent chronic conditions in populations of older ages. Previous studies have shown that hypertension and diabetes are risk factors for the development of cognitive impairment. However, the impact of hypertension combined with diabetes (HD) and their cumulative effects on cognitive impairment remain unclear. We aimed to investigate whether HD influences development of cognitive impairment and whether the effect is cumulative. Methods A case–control study was conducted. From 40,103 subjects aged 60 years or older, enrolled from 28 representative communities of 9 provinces of China between January 2015 and December 2021 into the Prevention and Intervention on Neurodegenerative Disease for Elderly in China program using multi-stage stratified random sampling, individuals not meeting our propensity score matching criteria were excluded, and 13,252 individuals were finally selected for the study. Exposure factors included hypertension, diabetes and their comorbidity. Odds ratios (ORs) of exposure factors on cognitive impairment were measured using multiple logistic regression. Results We found significant impacts of hypertension, diabetes and their comorbidity on cognitive impairment occurrence. The OR values for dementia were 1.18 for individuals with hypertension only, 1.26 for those with diabetes only, and 1.53 for those with HD. Compared to participants without hypertension and diabetes, the OR values for mild cognitive impairment (MCI) were 1.11 for individuals with hypertension only, 1.32 for those with diabetes only, and 1.27 for those with HD. For subjects with HD longer than 5 years, the comorbidity significantly impacted on MCI and dementia, and the degree of impact increased with the duration of comorbidity. For hypertension, the influence of hypertension on dementia were most influential in middle-aged (45–64 years old) people. By contrast, the influence of diabetes on people younger than 45-year-old was most significant, with the middle-age group being the second most impacted subjects. Conclusions The elderly with HD have a heightened risk of developing cognitive impairment, particularly dementia, compared to those with either hypertension or diabetes alone. The study revealed a significant cumulative impact of HD on cognitive impairment.